IL-33 as a Critical Cytokine for Inflammation and Fibrosis in Inflammatory Bowel Diseases and Pancreatitis - Kurimoto, Masayuki; Watanabe, Tomohiro; Kamata, Ken; Minaga, Kosuke; Kudo, Masatoshi (Frontiers in Physiology, 2021)
IL-33 is a pleiotropic cytokine that promotes inflammation and fibrosis. IL-33 is produced by a broad range of cells, including antigen-presenting cells, epithelial cells, and fibroblasts. IL-33 produced by the innate immune cells has been shown to activate pro-inflammatory T helper type 1 (Th1) and Th2 responses. The intestinal barrier and tolerogenic immune responses against commensal microbiota contribute to the maintenance of gut immune homeostasis. Breakdown of tolerogenic responses against commensal microbiota as a result of intestinal barrier dysfunction underlies the immunopathogenesis of inflammatory bowel diseases (IBD) and pancreatitis. Recent studies have provided evidence that IL-33 is an innate immune cytokine that bridges adaptive Th1 and Th2 responses associated with IBD and pancreatitis. In this Mini Review, we discuss the pathogenic roles played by IL-33 in the development of IBD and pancreatitis and consider the potential of this cytokine to be a new therapeutic target.